Implementation of Project Based Learning Model in Improving Students' Teamwork Skills in Elementary Schools - Siti Kaila Zahwa; Muhaiminah Jalal; Nisa Aulia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe the implementation of the Project Based Learning model and to improve the teamwork skills of fourth-grade students in Ilmu Pengetahuan Alam dan Sosial learning. This research employed Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were fourth-grade students of Sekolah Dasar Negeri 209/IV Kota Jambi. Data were collected through observation, documentation, and teamwork questionnaires. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the implementation of the Project Based Learning model in Ilmu Pengetahuan Alam dan Sosial learning improved students’ teamwork skills, as indicated by the increasing percentage of achievement in each cycle. Students also became more active, collaborative, and responsible in completing group tasks. Therefore, the Project Based Learning model is effective in enhancing the teamwork skills of fourth-grade students.